Synthesis and conformational analysis of N-aryl-N-(6-azulenyl)acetamides. Issue 29 (18th July 2019) - Ito, Ai; Ishii, Ayako; Amaki, Takamasa; Fukuda, Kazuo; Yamasaki, Ryu; Okamoto, Iwao
Graphical abstract: Highlights: Solution and crystal structures of N -aryl- N -(6-azulenyl)acetamides were determined. The relative π-electron densities of the N -aromatic groups affect the conformation. The N -(6-azulenyl) group has a very different effect from the N -(2-azulenyl) group. Abstract: We synthesized a series of N -(6-azulenyl)- N -arylacetamides, and investigated their conformational preferences in solution and in the crystalline state by means of NMR and X-ray analyses. The results indicated that the conformational preferences of these amides are dependent on both the relative π-electron densities of the N -aromatic parts and the three-dimensional relationship of the carbonyl group to the aryl groups. The N -(6-azulenyl) group has a very different effect from the previously reported N -(2-azulenyl) group on the conformational preferences of aromatic amides.